Supplementation with undegradable intake protein increases utilization of low-quality forage and microbial use of recycled urea - Wickersham, T.A.; Cochran, R.C.; Wickersham, E.E.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Low-quality forage utilization (intake and digestion) is improved by protein supplementation. Typically, the recommendation is to select supplements that are high in degradable intake protein because this fraction of the protein directly addresses the ruminal nitrogen deficiency that exists when low-quality forages are fed. However, the low cost of byproducts (e.g., distiller’s grains) that are high in undegradable intake protein makes them an attractive source of supplemental protein even though the response per unit of supplemental protein is less for undegradable protein than for degradable protein. One of the primary barriers to utilizing highly undegradable protein sources as supplements is the lack of information regarding their ability to provide nitrogen to ruminal microbes and, ultimately, their effectiveness as protein supplements to cattle fed low-quality forage. Because the protein is not ruminally degraded, the use of undegradable protein supplements to meet ruminal nitrogen requirements depends on the ability to recycle nitrogen to the rumen in the form of urea. Subsequently, the urea is utilized as a nitrogen source by ruminal microbes. Our objective was to measure how much nitrogen is recycled as urea and how much recycled nitrogen is used to meet microbial growth requirements when increasing amounts of undegradable intake protein were provided to steers consuming prairie hay. This data will be useful in developing supplementation strategies for cattle consuming low-quality forage.
Keywords: Beef; Cattle; Low-quality forage; Nitrogen; Urea